2011
DOI: 10.1371/journal.pgen.1002179
|View full text |Cite
|
Sign up to set email alerts
|

DAF-12 Regulates a Connected Network of Genes to Ensure Robust Developmental Decisions

Abstract: The nuclear receptor DAF-12 has roles in normal development, the decision to pursue dauer development in unfavorable conditions, and the modulation of adult aging. Despite the biologic importance of DAF-12, target genes for this receptor are largely unknown. To identify DAF-12 targets, we performed chromatin immunoprecipitation followed by hybridization to whole-genome tiling arrays. We identified 1,175 genomic regions to be bound in vivo by DAF-12, and these regions are enriched in known DAF-12 binding motifs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
76
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(80 citation statements)
references
References 72 publications
(106 reference statements)
2
76
0
2
Order By: Relevance
“…Using C. elegans, we and other researchers have demonstrated that NuRD-orchestrated anchor cell (AC) invasion programs could be relevant to metastasis [43,44]. These works would expand our understanding of the basis of metastasis.…”
Section: Genetics Of Nurds Invasion and Metastasismentioning
confidence: 69%
“…Using C. elegans, we and other researchers have demonstrated that NuRD-orchestrated anchor cell (AC) invasion programs could be relevant to metastasis [43,44]. These works would expand our understanding of the basis of metastasis.…”
Section: Genetics Of Nurds Invasion and Metastasismentioning
confidence: 69%
“…Therefore, the genetic programming of development includes mechanisms to ensure that developmental events occur flawlessly despite stressful conditions (1,2). Several studies indicate that microRNAs (miRNAs) are used to maintain the robustness of biological processes under stress conditions (3)(4)(5)(6)(7)(8)(9)(10). miRNAs are endogenous, noncoding, small RNAs that posttranscriptionally regulate gene expression primarily through binding to the 3′UTR of target mRNAs, which results in translation inhibition and/or mRNA degradation (11).…”
mentioning
confidence: 99%
“…[14,15] [17,19,20] Likely lacking of adaptive immunity in C. elegans. Autoimmune diseases [3] Genetically modified food safety Difference in natural corn and non-natural corn.…”
Section: Transgenic C Elegansmentioning
confidence: 99%
“…On one hand, a gene product in a lower model organism might possibly have a larger function profile, possibly as a potential divergent function (2 or n)-in-1 homolog in mammalian systems; on the other hand, the tightly regulated gene expression and finely adjustable concentrations of physiological material in humans may exacerbate the difference by adding new complexity due to natural selection. However, many innovative methods of overcoming such gaps allow model organisms to contribute greatly to our knowledge of human health and the means of addressing human diseases [1][2][3][4]. We briefly review some recent studies and discuss some novel challenges to overcome.…”
mentioning
confidence: 99%
See 1 more Smart Citation